Pain, sleep and emotional well-being explain the lack of agreement between physician- and patient-perceived remission in early rheumatoid arthritis - Samina A. Turk; Linda A. Rasch; Dirkjan van Schaardenburg; Willem F. Lems; Marjolein Sanberg; Lilian H. D. van Tuyl; Marieke M. ter Wee (BMC Rheumatology, 2018)
Abstract Background Clinical response and remission are defined in multiple ways and measured with different instruments, resulting in substantial variation of the proportion of patients classified as being in remission. Therefore, the agreement between patient-perceived, physician-perceived remission and clinical response and remission definitions was determined in early rheumatoid arthritis (RA) patients. And secondly, differences in clinical and patient-reported outcomes, in patients in physician-perceived remission, between patients in and not in self-perceived remission were assessed. Methods In 84 early RA patients, who received methotrexate and glucocorticoids, DAS44, ACR/EULAR Boolean-based remission, EULAR good and ACR70 response were determined after 12 weeks. Agreement between patient-perceived (phrased: “Would you say that, at this moment, your disease activity is as good as gone?”), physician-perceived remission (based on a visual analogue scale for global disease severity) and clinical response and remission definitions were calculated with the percentage of agreement and with kappa values (which corrects for change). In patients in physician-perceived remission, improvement in clinical and patient-reported outcomes (RAID) were compared between patients in and not in self-perceived remission. Results Agreement between the assessed outcome measures differed enormously. The agreement between physician-perceived and patient-perceived remission was 64% (kappa 0.25, p < 0.01). Physician-perceived remission had the best agreement with EULAR good response (79%), and patient-perceived remission with EULAR good and ACR70 response (both 69%). Patients not in self-perceived remission improved less on RAID components, especially on pain, sleep and emotional well-being. Conclusion One-third of the early RA patients disagreed with the physician on being in remission. Those patients had less improvement on RAID components, especially on pain, sleep and emotional well-being. Together with the variability in clinical response and remission definitions, these results highlight the need to increase patient involvement in their own health care decisions.